2016
DOI: 10.1021/acs.inorgchem.6b00592
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Plutonium(IV) and Uranium(VI) with N,N-Dialkyl Amides from Crystallography, X-ray Absorption Spectra, and Theoretical Calculations

Abstract: The structures of plutonium(IV) and uranium(VI) ions with a series of N,N-dialkyl amides ligands with linear and branched alkyl chains were elucidated from single-crystal X-ray diffraction (XRD), extended X-ray absorption fine structure (EXAFS), and theoretical calculations. In the field of nuclear fuel reprocessing, N,N-dialkyl amides are alternative organic ligands to achieve the separation of uranium(VI) and plutonium(IV) from highly concentrated nitric acid solution. EXAFS analysis combined with XRD shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 60 publications
(157 reference statements)
5
53
1
Order By: Relevance
“…The experimental spectra clearly differ from the typical uranyl spectra previously recorded from solvent extraction experiments: [10][11][12] in addition to the first U-Oax contribution from the linear transdioxo bonds (R + = 1.2 Å) and to the equatorial oxygen shell (R +  = 1.8 to 2.4 Å) the spectra exhibit unusual intense contributions in the second coordination sphere (R + > 2.5 Å). Considering the extraction equilibrium (eqn (1)), this feature could be due to the sulfur atoms from the sulfate anions coordinated with UO2 2+ .…”
Section: Probing the Existence Of Uranyl Trisulfate Structures In Thecontrasting
confidence: 75%
“…The experimental spectra clearly differ from the typical uranyl spectra previously recorded from solvent extraction experiments: [10][11][12] in addition to the first U-Oax contribution from the linear transdioxo bonds (R + = 1.2 Å) and to the equatorial oxygen shell (R +  = 1.8 to 2.4 Å) the spectra exhibit unusual intense contributions in the second coordination sphere (R + > 2.5 Å). Considering the extraction equilibrium (eqn (1)), this feature could be due to the sulfur atoms from the sulfate anions coordinated with UO2 2+ .…”
Section: Probing the Existence Of Uranyl Trisulfate Structures In Thecontrasting
confidence: 75%
“…Recent studies have suggested high nitric acid concentration increases the amount of p rotonated monoamide ligands (HL) in the organic phase, bringing about an outer-sphere coordination environment. 15,16 Similarly, elevated nitric acid conditions give rise to anionic trinitrate uranyl species, [UO 2 (NO 3 ) 3 ] -. 17,18 The mixed 1:1 and 1:2 stoichiometry could be due a protonated monoamide complexing with anionic uranyl (UO 2 (NO 3 ) 3 HL) and neptunyl species while the 1:2 ratio is synonymous with two ligands extracting the neutral hexavalent actinide dinitrate species (UO 2 (NO 3 ) 2 L 2 ).…”
Section: Ce (Iv) Extraction Using Dehba and Dehibamentioning
confidence: 99%
“…Siddall et al 6 have demonstrated that a simple modification of the acyl group can suppress Pu(IV) extraction. [18][19][20] In the series R = CH 3 , C 2 H 5 , CH(CH 3 ) 2 , C(CH 3 ) 3 , Pu(IV) distribution ratio D Pu continuously drops from 21 (R = CH 3 ) to 0.001 (R = C(CH 3 ) 3 ), while U(VI) distribution coefficient decreases much less significantly from 9.9 to 0.6 (upon extraction from a 3 M nitric acid aqueous solution to a toluene organic phase with 0.5 M of amide extractant). 6 Accordingly, U/Pu separation factor increases from 0.5 to ~600.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have revealed that plutonium extraction with amide derivatives is more complex than with TBP. 17,19 By coupling UV-Vis spectroscopy, EXAFS and quantum chemical calculations, it has been shown that the plutonium hexanitrato complex Pu(NO 3 ) 6…”
Section: Introductionmentioning
confidence: 99%